Contaminantes en el proceso de operación del mercado de mariscos "Las Mercedes" de Babahoyo y sus efectos en el producto pesquero y el ambiente, año 2014. Plan de manejo ambiental - Urdaningo Zambrano, Juan Pablo (2015)
Inadequate practices in the handling of fishery products in the following phases: capturing, transporting, processing and marketing, cause deterioration and contamination of the fishery resource. Improper waste management process seafoods market operation produces pollution. The present research was to study the contaminants in the operation process seafood market in Babahoyo city, their effects on fishery products and the environment. Field research was conducted with the participation and cooperation of fishermen, traders and regulators of fishing. Collections of samples of fish species were performed Dica (Pseudocurimata spp) through field trips, records and inspections seafood market. Collected samples were sent to certified laboratories for analysis. Data were recorded from June to November 2014 in the seafood market "Las Mercedes" of Babahoyo city province of Los Ríos, Ecuador. Environmental impact matrix cause-effect was designed to determine the magnitude of impact to the environment. It was found that wastewater generated seafood market are higher than the provisions of the environmental standard BOD 1672.8mg/l (n=5) values, COD 2592mg/l (n=5) and Oils and Fats 798.02 mg/l (n=5). Fish samples collected showed high rates of chemical and microbiological contamination Aerobic Mesophilic 3,25E+5cfu/g (n=15) of E. Coli 1,34E+3cfu/g (n=15); presence of Salmonella sp. in 10 samples of fresh fish (n=15). Public health (-22) is the factor with the greatest negative involvement, with significant involvements on water quality (-19), the reception phase (-30) produced the greatest negative impacts to the environment, primarily on factors: physical and socio-culturally. The total negative impacts (-87) was greater than the positive (24) resulting in the Environmental Impact Study (-63) rated "Moderately Significant Negative". Keywords: Dica, pollution, environmental impact.